2003
DOI: 10.5144/0256-4947.2003.132
|View full text |Cite
|
Sign up to set email alerts
|

Five Year Experience in Prenatal Ultrasound Diagnosis of Esophageal Atresia in Saudi Arabia

Abstract: Background: Esophageal atresia (EA), with or without tracheoesophageal fistula (TOF) is one of themost correctable fetal anomalies if diagnosed antenatally by serial ultrasound. We retrospectivelyevaluated antenatal diagnoses by ultrasound of EA with or without TOF at our institution in SaudiArabia. Patients and Methods:We examined the records of mothers and infants with EA with or without TOFwho were booked early and delivered at our institution during 1994 to 1998. Fetal diagnosis wasbased on level II serial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The second reason for achieving an improved survival is thanks to an ever increasing antenatal diagnosis. 5 An antenatal diagnosis results in immediate neonatal care, and pulmonary complications can also be avoided. However, there are pseudopositive cases as well as pseudonegative cases.…”
Section: Esophageal Atresiamentioning
confidence: 99%
“…The second reason for achieving an improved survival is thanks to an ever increasing antenatal diagnosis. 5 An antenatal diagnosis results in immediate neonatal care, and pulmonary complications can also be avoided. However, there are pseudopositive cases as well as pseudonegative cases.…”
Section: Esophageal Atresiamentioning
confidence: 99%
“…Many studies found the incidence of congenital abnormalities to be 23/1000 live births. The incidence for birth defects of the gastrointestinal tract was 1.3 per 1000 live births, for neural tube defects (NTD) 1.9/1000 live births, and for Down’s syndrome 1.8 per 1000 live births [10-13]. …”
Section: Introductionmentioning
confidence: 99%
“…11 Another study found the incidence of congenital abnormalities to be 23/1000 live births. 12 The incidence for congenital malformation of the gastrointestinal tract was 1.3 per 1000 live births, 13 for neural tube defects (NTD) 1.9/1000 live births, 14 and for Down' s syndrome 1.8 per 1000 live births. 15 The exact antenatal prevalence of major congenital anomalies in Saudi Arabia and the prognosis of those anomalies have not been reported.…”
mentioning
confidence: 99%